Creditor Protection and Financial Cycles - Arturo Galindo; Alejandro Micco (Inter-American Development Bank, Research Department, 2001)
We develop a model in which the elasticity of credit to exogenous shocks depends on creditor rights regulations. We show that an increase in creditor protection reduces the elasticity of credit supply to exogenous shocks, and hence the amplitude of the credit cycle. Using an extended set of a measure of creditor rights protection in the spirit of La Porta et al. (1998), we find that stricter creditor rights regulations not only increase the breadth of the credit market but also reduce the volatility of the credit cycle.
Keywords: 330; Gläubigerschutz; Kredit; Angebot; Schock; Theorie